Knowledge and hiv/aids at risk behaviour of collegiate athletes to the 2007 edition of zone c nicega preliminaries held at college of education, oro (2007)
This study was embarked upon to investigate the knowledge and HIV/AIDS At-Risk behaviour of Collegiate Athletes that participated in the 2007 Edition of the NICEGA Zonal Elimination Preliminaries held between 4th and 8,h July, 2007 at College of Education, Oro. This study became necessary owing to the fact that despite several campaigns on the pandemic nature of HIV/AIDS many athletes are still observed exhibiting HIV/AIDS At-Risk behaviour during pre-camping, camping, competition, and even post competition periods. The study adopted descriptive survey research design, while quota or maximum variation sampling technique was used to select the respondents; simple random sampling technique was used to select 5 sports. Descriptive Statistics of frequency counts, percentage and inferential statistics were used to analyse the collected data at 0.05 level of significance. The findings from the study revealed that all the tested variables; Knowledge, Cohabitation, Unprotected Sex, and Sexual Networking were significant. Based on the finding of this study conclusions were drawn and useful recommendations were suggested